PENYELESAIAN SENGKETA WALI ADHAL DAN KAITANNYA DENGAN KEABSAHAN PERKAWINAN (STUDI TERHADAP PENETAPAN NO. 215/PDT.P/2011/P.A.JAKARTA SELATAN) - SYLVANA AMELIA FAUZI (PREMISE LAW JURNAL, 2016)
Wali nikah (male next of kin and guardian whose consent is required for the marriage of a girl or woman) is one of the pillars of marriage, and it is written in Article 14 of the Compilation of Islamic Law. Rasulullah SAW said that “the marriage is not valid without the (present of ) wali” meaning that the marriage agreement is not valid without the present of guardian. In general, the one who becomes the wali for the marriage is wali nasab. If the wali nasab is adhal (fair), the guardianship can be represented by wali hakim. The transfer of guardianship from wali nasab to wali hakimis regulated in Article 23 (1) and (2) of the Compilation of Islamic Law. The purpose of this study was to describe the factors causing the incident of wali adhal, the validity of marriage if the wali adhal occured based on the decision No. 215/Pdt.P/2011/Pengadilan Agama Jakarta Selatan, and the status of marriage resulted from the wali adhal marriage. Keywords : Wali Adhal, Validity, Marriage